![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
Differentiate \[\left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\], with respect to x.
Answer
513.6k+ views
Hint- Here, we will proceed by simplifying the given function (which needs to be differentiated) with the help of a proper substitution.
Let the function be \[y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\]
Put $x = a\sin \theta $ in the above function, we get
\[ \Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2} - {{\left( {a\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2}\left[ {1 - {{\left( {\sin \theta } \right)}^2}} \right]} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right]\]
As, we know that ${\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1 \Rightarrow 1 - {\left( {\sin \theta } \right)^2} = {\left( {\cos \theta } \right)^2}$
Using this above identity to simplify the function whose differentiation needs to be carried out
\[
\Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\sqrt {{{\left( {\cos \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\cos \theta }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\tan \theta } \right)} \right] = \theta \\
\Rightarrow y = \theta {\text{ }} \to {\text{(1)}} \\
\]
Also, we know that $x = a\sin \theta \Rightarrow \sin \theta = \dfrac{x}{a} \Rightarrow \theta = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(2)}}$
Substituting the value obtained from equation (2) in equation (1), we get
\[ \Rightarrow y = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(3)}}\]
Also we know that $\dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {f\left( x \right)} \right)} \right]}}{{dx}} = \left[ {\dfrac{1}{{\sqrt {1 - {{\left( {f\left( x \right)} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {f\left( x \right)} \right)}}{{dx}}} \right]$
Differentiating both sides of equation (3) with respect to $x$, we get
\[
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {\dfrac{x}{a}} \right)} \right]}}{{dx}}{\text{ = }}\left[ {\dfrac{1}{{\sqrt {1 - {{\left( {\dfrac{x}{a}} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {\dfrac{x}{a}} \right)}}{{dx}}} \right] = \left[ {\dfrac{1}{{\sqrt {\left( {\dfrac{{{a^2} - {x^2}}}{{{a^2}}}} \right)} }}} \right] \times \left[ {\dfrac{1}{a}} \right] = \left[ {\dfrac{a}{{\sqrt {{a^2} - {x^2}} }}} \right] \times \left[ {\dfrac{1}{a}} \right] \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{1}{{\sqrt {{a^2} - {x^2}} }} \\
\]
Therefore, the differentiation of the given function \[\left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\], with respect to $x$ is \[\dfrac{1}{{\sqrt {{a^2} - {x^2}} }}\].
Note- In this problem we have especially substituted $x = a\sin \theta $ because due to this substitution, the function inside the tangent inverse will be converted into tangent so that these two will cancel out with each other and we will be left with the angle which is in a much simplified form.
Let the function be \[y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\]
Put $x = a\sin \theta $ in the above function, we get
\[ \Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2} - {{\left( {a\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{\sqrt {{a^2}\left[ {1 - {{\left( {\sin \theta } \right)}^2}} \right]} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right]\]
As, we know that ${\left( {\sin \theta } \right)^2} + {\left( {\cos \theta } \right)^2} = 1 \Rightarrow 1 - {\left( {\sin \theta } \right)^2} = {\left( {\cos \theta } \right)^2}$
Using this above identity to simplify the function whose differentiation needs to be carried out
\[
\Rightarrow y = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{a\sin \theta }}{{a\sqrt {1 - {{\left( {\sin \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\sqrt {{{\left( {\cos \theta } \right)}^2}} }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\dfrac{{\sin \theta }}{{\cos \theta }}} \right)} \right] = \left[ {{{\tan }^{ - 1}}\left( {\tan \theta } \right)} \right] = \theta \\
\Rightarrow y = \theta {\text{ }} \to {\text{(1)}} \\
\]
Also, we know that $x = a\sin \theta \Rightarrow \sin \theta = \dfrac{x}{a} \Rightarrow \theta = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(2)}}$
Substituting the value obtained from equation (2) in equation (1), we get
\[ \Rightarrow y = {\sin ^{ - 1}}\left( {\dfrac{x}{a}} \right){\text{ }} \to {\text{(3)}}\]
Also we know that $\dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {f\left( x \right)} \right)} \right]}}{{dx}} = \left[ {\dfrac{1}{{\sqrt {1 - {{\left( {f\left( x \right)} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {f\left( x \right)} \right)}}{{dx}}} \right]$
Differentiating both sides of equation (3) with respect to $x$, we get
\[
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{d\left[ {{{\sin }^{ - 1}}\left( {\dfrac{x}{a}} \right)} \right]}}{{dx}}{\text{ = }}\left[ {\dfrac{1}{{\sqrt {1 - {{\left( {\dfrac{x}{a}} \right)}^2}} }}} \right] \times \left[ {\dfrac{{d\left( {\dfrac{x}{a}} \right)}}{{dx}}} \right] = \left[ {\dfrac{1}{{\sqrt {\left( {\dfrac{{{a^2} - {x^2}}}{{{a^2}}}} \right)} }}} \right] \times \left[ {\dfrac{1}{a}} \right] = \left[ {\dfrac{a}{{\sqrt {{a^2} - {x^2}} }}} \right] \times \left[ {\dfrac{1}{a}} \right] \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{1}{{\sqrt {{a^2} - {x^2}} }} \\
\]
Therefore, the differentiation of the given function \[\left[ {{{\tan }^{ - 1}}\left( {\dfrac{x}{{\sqrt {{a^2} - {x^2}} }}} \right)} \right]\], with respect to $x$ is \[\dfrac{1}{{\sqrt {{a^2} - {x^2}} }}\].
Note- In this problem we have especially substituted $x = a\sin \theta $ because due to this substitution, the function inside the tangent inverse will be converted into tangent so that these two will cancel out with each other and we will be left with the angle which is in a much simplified form.
Recently Updated Pages
Master Class 12 Economics: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 12 Maths: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 12 Biology: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 12 Physics: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 12 Business Studies: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 12 English: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
Which are the Top 10 Largest Countries of the World?
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Draw a labelled sketch of the human eye class 12 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is the Full Form of PVC, PET, HDPE, LDPE, PP and PS ?
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What is a transformer Explain the principle construction class 12 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What are the major means of transport Explain each class 12 social science CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)